Family Firms and Research and Development Investment: The Moderator Effect of the Board Composition - Briano-Turrent, Guadalupe del Carmen; Watkins-Fassler, Karen; Rodríguez-Ariza, Lázaro; Reyes-Bastidas, Carolina (European Journal of Family Business, 2023)
From the perspective of agency and socio-emotional theories, the family firm’s innovation behavior differs from non-family companies. We investigate the relationship between the family element and Research and Development (R&D) investment, and how the moderating effect of the board composition affects this relationship. Using a panel data composed by 1,284 observations-year during the period 2004-2014 from Argentina, Brazil, Chile and Mexico, empirical results show that family firms increase R&D investment when the moderating effect of the board composition is included. For instance, larger boards, the independence of the board, the COB-CEO duality and female directors motivates to a higher R&D and capital expenditures. These results confirm that board composition constitutes a monitoring mechanism of family members' actions, which leads to an increase of innovation strategies and suggest that family firms promote a long-term orientation with the purpose of preserving the wealth for next generations. This research contributes to the international literature analyzing a region not explored before and characterized by a weak institutional framework and lower rates on R&D investment compared to other emerging countries.